2017
DOI: 10.4102/phcfm.v9i1.1368
|View full text |Cite
|
Sign up to set email alerts
|

Mapping evidence of interventions and strategies to bridge the gap in the implementation of the prevention of mother-to-child transmission of HIV programme policy in sub-Saharan countries: A scoping review

Abstract: BackgroundPrevention of mother-to-child transmission (PMTCT) of HIV is a life-saving public health intervention. Sub-Saharan African (SSA) countries have made significant progress in the programme, but little is known about the strategies used by them to eliminate mother-to-child transmission of HIV.AimTo map evidence of strategies and interventions employed by SSA in bridging the implementation gap in the rapidly changing PMTCT of HIV programme policy.MethodsElectronic search of the databases MEDLINE, PubMed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 51 publications
1
12
1
Order By: Relevance
“…48 49 Participants, all of whom occupy responsible management positions, described governance gaps affecting CPG implementation, a factor also identified in other studies in sub-Saharan African countries. 50 Participants described volumes of incoming policies without time for consultation, adaptation or planning; and rushed implementation responding to political drivers rather than healthcare quality considerations. To address this challenge, managers often partnered with community leaders and NGOs.…”
Section: Discussionmentioning
confidence: 99%
“…48 49 Participants, all of whom occupy responsible management positions, described governance gaps affecting CPG implementation, a factor also identified in other studies in sub-Saharan African countries. 50 Participants described volumes of incoming policies without time for consultation, adaptation or planning; and rushed implementation responding to political drivers rather than healthcare quality considerations. To address this challenge, managers often partnered with community leaders and NGOs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that uptake of PMTCT services and psychosocial support were the main target of the identified interventions, followed by interventions to increase ART initiation and EID. Importantly, WLH require knowledge on PMTCT, how to care for their exposed infants and how to live healthy [7, 17, 20, 21, 46, 47]. This may be attributed to countries in SSA putting greater emphasis on elimination of mother-to-child transmission of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence to support the effectiveness of utilising LHWs to improve certain MCH indices such as promotion of breastfeeding, and increased uptake of childhood immunisation and cervical cancer screening, evidence remains scanty on the role of LHWs in several other specific MCH interventions such as those for HIV positive mother-HEI pairs [7]. As Sub-Saharan African (SSA) countries strengthen their systems towards elimination of mother to child transmission (elimination of mother-to-child transmission) of HIV, efforts to identify ways to improve utilisation of LHWs to deliver further MCH services that encompass all aspects of the needs of HIV positive mother and the exposed baby pairs should be intensified.…”
Section: Introductionmentioning
confidence: 99%
“…Peltzer et al [17] noted that successful PMTCT interventions in South Africa have included mother-to-mother peer mentoring as well as cognitive behavioral interventions [18]. Male involvement in PMTCT was also seen as improving PMTCT outcomes [19] as well as interventions that involved numerous text messages and telephone calls to pregnant women reminding them of PMTCT [20]. In the 51 study meta-analysis of ART adherence during and after pregnancy, facilitators of better adherence included higher education, higher income, knowledge about PMTCT, previous PMTCT, disclosure of HIV status, positive partner support, support groups, and being on lifelong ART [12].…”
Section: Introductionmentioning
confidence: 99%